Effect of Type of Commodity on the Capacity of Multifucer Roller - Fadli Elsyah Pasaribu; Saipul Bahri Daulay; Ainun Rohanah (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Milling is done to powder food with a certain level of refinement to be more easily processed into other products. This study was conducted to test the capacity of the equipment using several commodities in multifucer grinder. Sorghum, soybeans, and rice were commodities to be tested to determine the effective capacity,the percentage of material not accommodated, and efficiency of the equipment. The results showed that the effective tool capacity was 19.48k/h for sorghum, 12.22k/h for soybean and 24.35 kg/h for rice. Percentage of material that was not accommodated was 7.33% for sorghum, 6.66% for soybean and 4,16% for rice. Appliance efficiency percentage was 92.66% for sorghum, 93.33% for soybean and 95.83% for rice. Keywords: Multifucer, Sorghum, Soybeans, Rice.